Groundwater-corrosion-resistant cement-soil mixing pile curing agent and preparation method thereof

By using geopolymer materials to replace traditional cement and combined with industrial waste resource utilization, the problems of insufficient durability and carbon emissions of cement soil mixing piles in groundwater environments are solved, and efficient, environmentally friendly and economical curing agent applications are achieved.

CN119306433APending Publication Date: 2025-01-14STATE GRID JIANGXI ELECTRIC POWER CO LTD ECONOMIC & TECH RES INST +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411442333.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

Traditional cement soil mixing piles have insufficient durability in groundwater environments, and high carbon emissions in cement production have an impact on the environment. It is urgent to develop environmentally friendly alternative curing agents.

Method used

The geopolymer material is used as the curing agent, and the polymerization reaction of aluminum silicon material and alkaline exciter under normal temperature conditions is used to replace traditional cement, improve the compressive strength and durability of the pile body, and utilize industrial waste resource utilization to reduce Carbon dioxide emissions.

Benefits of technology

Geopolymer curing agents significantly improve the resistance to erosion of sulfates, carbonates and acidic water in groundwater, reduce maintenance costs, reduce carbon emissions and natural resource exploitation, and achieve the improvement of environmental protection and economic benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005086671670000111
    Figure BDA0005086671670000111
  • Figure BDA0005086671670000121
    Figure BDA0005086671670000121
Patent Text Reader

Abstract

The invention discloses a cement-soil mixing pile curing agent resistant to underground water corrosion and a preparation method of the cement-soil mixing pile curing agent, montmorillonite, mineral powder, fly ash, carbide slag and other industrial byproducts are adopted to replace traditional cement to serve as main curing materials, and the curing agent is prepared through different proportions. The curing material comprises 1-5 parts of montmorillonite, 10-20 parts of carbide slag and 70-85 parts of mineral powder and fly ash, and the ratio of the mineral powder to the fly ash is 7: 3-9: 1. And 8-12 parts of a sodium water glass alkali activator, wherein the modulus is 0.8-1.2. Compared with a traditional cement curing agent, the geopolymer curing agent disclosed by the invention not only can meet the mechanical property of the cement-soil mixing pile, but also has excellent underground water erosion resistance, and the applicability of the cement-soil mixing pile is enhanced. In addition, the curing agent disclosed by the invention has a remarkable environmental protection advantage, reduces carbon emission, can effectively utilize industrial by-products, provides a new thought for realizing green construction and sustainable development, and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and in particular relates to a cement-soil mixing pile curing agent and a curing method resistant to groundwater corrosion. Background Art

[0002] In civil engineering, cement-soil mixing pile technology is a commonly used method for foundation reinforcement and soil improvement. Cement, used as a curing agent, is mixed with in-situ soil to form a composite pile with a certain strength and stability. This technology can effectively improve the bearing capacity and stability of foundations and is therefore widely used in soft soil foundation treatment, slope reinforcement, and foundation pit support projects. However, conventional cement-soil mixing pile curing agents that are resistant to groundwater corrosion are mostly based on cement. While they offer good initial strength, the sulfates, carbonates, and acidic water in groundwater significantly affect the durability of cement-soil mixing piles in complex environments, often resulting in insufficient durability when used with conventional cement. Furthermore, the high carbon emissions from cement production have a significant impact on the environment, necessitating the development of alternative curing agents to meet the requirements of sustainable development. Therefore, the search for an environmentally friendly curing agent that can replace traditional cement to combat groundwater erosion on conventional cement-soil mixing piles is a key research direction in civil engineering. Summary of the Invention

[0003] In order to solve the above problems, the present invention discloses a cement-soil mixing pile curing agent resistant to groundwater corrosion and a preparation method thereof. The present invention adopts geopolymer materials to replace traditional cement-based curing agents to improve the durability and environmental friendliness of the pile body in the groundwater environment. Geopolymer is a new type of inorganic polymer material, which is produced by polymerization reaction of aluminum-silica materials (such as fly ash, slag) and alkaline activators (such as sodium hydroxide, potassium hydroxide) under normal temperature conditions. Compared with traditional cement curing agents, the geopolymer curing agent of the present invention can meet the compressive strength of the pile body on the one hand, and at the same time can better resist the erosion of components such as sulfates, carbonates and acidic water in groundwater, thereby improving the durability of the mixing pile; on the other hand, the production process of geopolymer does not require high-temperature calcination, which can greatly reduce carbon dioxide emissions. At the same time, industrial waste (such as fly ash and slag) is utilized to realize the resource utilization of industrial solid waste, which makes geopolymer a green and environmentally friendly building material, which helps to promote the development of the civil engineering field in a more environmentally friendly and economical direction.

[0004] To achieve the above object, the technical solution adopted by the present invention is:

[0005] A cement-soil mixing pile curing agent resistant to groundwater corrosion comprises, by weight, 1 to 5 parts of montmorillonite, 10 to 20 parts of carbide slag, 70 to 85 parts of a mixture of mineral powder and fly ash, and 8 to 12 parts of a sodium silicate activator; the mass ratio of the mineral powder to the fly ash in the mixture is 7:3 to 9:1.

[0006] As a further improvement, the mineral powder is S95 mineral powder, and the activity indexes at 7 days and 28 days are 412% and 86% respectively.

[0007] A further improvement is that the fly ash is Class F II fly ash with a fineness of 20%.

[0008] As a further improvement, the montmorillonite has a particle size of 1-10 microns and a purity of more than 90%.

[0009] As a further improvement, the modulus of the sodium silicate activator is 0.8 to 1.2.

[0010] A method for preparing a cement-soil mixing pile curing agent resistant to groundwater corrosion comprises the following steps:

[0011] Step 1: Raw material preparation: Prepare the raw materials according to the above-mentioned formula of cement-soil mixing pile curing agent resistant to groundwater corrosion;

[0012] Step 2: Adjust the modulus: Use an instrument to measure the modulus of the sodium silicate activator and ensure that it is within the range of 0.8 to 1.2; if the modulus is too high, add NaOH solution to reduce the modulus; if the modulus is too low, add sodium silicate solution to increase the modulus to obtain the sodium silicate activator;

[0013] Step 3: Mix ratio design: weigh the raw materials according to the formula of the cement-soil mixing pile curing agent resistant to groundwater corrosion according to any one of claims 1-5;

[0014] Step 4: Mix the weighed montmorillonite, carbide slag, mineral powder and fly ash and stir at low speed for 2 to 3 minutes to ensure that the mixture is uniform to obtain a precursor;

[0015] Step 5: Add sodium silicate alkali activator to the precursor and continue stirring for 5 to 10 minutes to obtain a cement soil mixing pile curing agent resistant to groundwater corrosion.

[0016] As a further improvement, in step 4, a stirrer is used for low-speed stirring, and the rotation speed of the low-speed stirring is 48 rpm; in step 5, the stirring speed is 100 rpm.

[0017] A method for using a cement-soil mixing pile curing agent resistant to groundwater corrosion, the cement-soil mixing pile curing agent resistant to groundwater corrosion as described above; in the step 5, a sodium silicate alkali activator is mixed with water so that the water-binder ratio reaches 0.6, and then the precursor is added and stirred for 5 to 10 minutes to obtain the cement-soil mixing pile curing agent resistant to groundwater corrosion, which is then added to an in-situ soil sample and stirred evenly. After stirring is completed, the curing is carried out naturally, and after curing is completed, the quality of the mixing pile needs to be tested; wherein, the mass of the cement-soil mixing pile curing agent resistant to groundwater corrosion is 20% of the in-situ soil sample.

[0018] The advantages of the present invention are as follows:

[0019] a. Excellent resistance to groundwater erosion: Components in groundwater (such as sulfates, carbonates, etc.) are significantly corrosive to traditional cement-based materials, while geopolymers have extremely strong resistance to corrosive media such as acids, carbonates, and sulfates. Geopolymer materials, due to their dense three-dimensional silicon aluminum oxide structure, do not react with these corrosive substances, and can better resist chemical erosion in groundwater, extend the service life of the pile body, and reduce maintenance costs. At the same time, since montmorillonite has good water absorption, expansion, adsorption and adhesion, it can increase the density of the material, improve the strength of the material, and can also capture sulfate ions to reduce the erosion of sulfate on the geopolymer structure. The present invention adds an appropriate amount of montmorillonite to improve the corrosion resistance of the curing agent. Compared with traditional cement, the curing agent of the present invention is not easy to react chemically, so it has a wider range of applications.

[0020] B, significant environmental benefits: the curing agent of the present invention significantly improves environmental benefits, and its main raw materials are industrial by-products such as fly ash, slag, etc., which effectively reduce the exploitation and dependence on natural resources, and alleviate the environmental pressure brought by the accumulation of industrial waste. In addition, the curing agent production process of the present invention does not require high-temperature calcination, avoids a large amount of carbon dioxide emissions in the traditional cement production process, and significantly reduces the impact on the environment in the production process. Therefore, the present invention can not only effectively reduce carbon emissions, but also promote the recycling of resources, in line with the concept of green building and low-carbon environmental protection.

[0021] c. Significant Economic Benefits: The geopolymer curing agent of the present invention offers significant economic benefits. Its primary component is low-cost industrial waste, making it less expensive than traditional cement raw materials. Furthermore, it requires no high-temperature calcination, significantly reducing energy consumption and costs during production. Furthermore, the curing agent of the present invention performs exceptionally well in complex environments, particularly groundwater environments, effectively avoiding the risk of premature failure of traditional materials and thus reducing potential repair costs. Overall, the geopolymer curing agent of the present invention not only reduces initial construction costs but also lowers long-term operating and maintenance costs, resulting in significant economic benefits. DETAILED DESCRIPTION

[0022] The montmorillonite of the present invention was purchased from Hongyao Mineral Products Co., Ltd., carbide slag was purchased from Rongsong Construction Engineering Co., Ltd., mineral powder was purchased from Borun Casting Materials Co., Ltd., fly ash was purchased from Gongyi Longze Water Purification Materials Co., Ltd., sodium water glass was purchased from Jiangsu Yubang New Materials Technology Co., Ltd., and hydrochloric acid and sodium sulfate were purchased from Dengfeng Chemical Reagent Factory.

[0023] The uses of the various components of the curing agent of the present invention are as follows:

[0024] a. Mineral powder and fly ash: The combination of the two is 70-85 parts by weight, with a mineral powder to fly ash ratio of 7:3-9:1. Mineral powder is highly reactive, especially when activated by an alkaline activator, rapidly developing strength. The calcium ions react with silica-alumina to form a CASH gel. The silica-alumina in fly ash, when activated by an alkaline activator, forms a NASH gel, which improves the material's fluidity and long-term strength.

[0025] b. Montmorillonite: 1-5 parts by weight. Montmorillonite is a layered silicate mineral. Its layered structure expands and fills pores after absorbing water, helping to increase the density of the geopolymer and reduce porosity. Montmorillonite also effectively absorbs corrosive ions such as chloride and sulfate, preventing them from entering the geopolymer's internal structure, thereby improving the material's resistance to chemical attack.

[0026] c. Carbide slag: 10 to 20 parts by weight. The main component of carbide slag is calcium oxide (CaO), which can play a role similar to that of an auxiliary alkaline activator, increase the alkalinity of the system, promote the dissolution of silicon and aluminum oxides in fly ash and slag, and accelerate the polymerization reaction.

[0027] d. Sodium water glass: 8-12 parts by weight, with a modulus of 0.8-1.2. As an activator, sodium water glass plays a key role in the curing agent system. By providing a strong alkaline environment, it stimulates the pozzolanic activity of the mineral powder and fly ash, promoting the formation of a high-strength CSH gel.

[0028] The immersion solution for the corrosion resistance test of the present invention is an acidic solution and a sulfate solution. HCl is used to prepare an acidic solution with a pH of 5, and sodium sulfate (Na2SO4) is used to prepare a sulfate solution with a concentration of 5%.

[0029] Example 1:

[0030] Weigh 5 parts by weight of montmorillonite, 10 parts by weight of carbide slag, and 85 parts by weight of mineral powder and fly ash in a 9:1 ratio. Mix and stir at low speed for 2-3 minutes to prepare a solid waste mixture (precursor). Add 8 parts by weight of 0.8 modulus sodium water glass and set aside. Add an alkaline activator and an appropriate amount of water (to achieve a water-binder ratio of 0.6) to the weighed solid waste mixture and stir for 5 minutes to obtain a curing agent. Add the in-situ soil sample to the curing agent and stir evenly. The amount of curing agent added is 20% of the in-situ soil sample mass, and the amount of alkaline activator added is 8% of the precursor mass.

[0031] Example 2:

[0032] Weigh 5 parts by weight of montmorillonite, 10 parts by weight of carbide slag, and 85 parts by weight of mineral powder and fly ash, and weigh them in a ratio of 9:1. Mix and stir at low speed for 2 to 3 minutes to prepare a solid waste mixture (precursor); prepare 10 parts by weight of 0.8 modulus sodium water glass and set aside. Then add an alkali activator and an appropriate amount of water (so that the water-binder ratio reaches 0.6) to the weighed solid waste mixture and stir for 5 minutes to obtain a curing agent. Then add the in-situ soil sample to the curing agent and stir evenly. The amount of curing agent added is 20% of the mass of the in-situ soil sample; the amount of alkali activator added is 10% of the precursor.

[0033] Example 3:

[0034] Weigh 5 parts by weight of montmorillonite, 10 parts by weight of carbide slag, and 85 parts by weight of mineral powder and fly ash, and weigh them in a ratio of 9:1. Mix and stir at low speed for 2 to 3 minutes to prepare a solid waste mixture (precursor); prepare 12 parts by weight of 0.8 modulus sodium water glass and set aside. Then add an alkali activator and an appropriate amount of water (so that the water-binder ratio reaches 0.6) to the weighed solid waste mixture and stir for 5 minutes to obtain a curing agent. Then add the in-situ soil sample to the curing agent and stir evenly. The amount of curing agent added is 20% of the mass of the in-situ soil sample; the amount of alkali activator added is 12% of the precursor.

[0035] Example 4:

[0036] Weigh 5 parts by weight of montmorillonite, 10 parts by weight of carbide slag, and 85 parts by weight of mineral powder and fly ash in a ratio of 9:1. Mix and stir at low speed for 2 to 3 minutes to prepare a solid waste mixture (precursor). Add 12 parts by weight of 1.0 modulus sodium water glass and set aside. Then add an alkaline activator and an appropriate amount of water (so that the water-binder ratio reaches 0.6) to the weighed solid waste mixture and stir for 5 minutes to obtain a curing agent. Then add the in-situ soil sample to the curing agent and stir evenly. The amount of curing agent added is 20% of the mass of the in-situ soil sample; the amount of alkaline activator added is 12% of the precursor.

[0037] Example 5:

[0038] Weigh 5 parts by weight of montmorillonite, 10 parts by weight of carbide slag, and 85 parts by weight of mineral powder and fly ash in a ratio of 9:1. Mix and stir at low speed for 2 to 3 minutes to prepare a solid waste mixture (precursor); prepare 12 parts by weight of 1.2 modulus sodium water glass and set aside. Then add an alkali activator and an appropriate amount of water (so that the water-binder ratio reaches 0.6) to the weighed solid waste mixture and stir for 5 minutes to obtain a curing agent. Then add the in-situ soil sample to the curing agent and stir evenly. The amount of curing agent added is 20% of the mass of the in-situ soil sample; the amount of alkali activator added is 12% of the precursor.

[0039] Example 6:

[0040] Weigh 5 parts by weight of montmorillonite, 10 parts by weight of carbide slag, and 85 parts by weight of mineral powder and fly ash, and weigh them in a ratio of 8:2. Mix and stir at low speed for 2 to 3 minutes to prepare a solid waste mixture (precursor); prepare 12 parts by weight of 0.8 modulus sodium water glass and set aside. Then add an alkali activator and an appropriate amount of water (so that the water-binder ratio reaches 0.6) to the weighed solid waste mixture and stir for 5 minutes to obtain a curing agent. Then add the in-situ soil sample to the curing agent and stir evenly. The amount of curing agent added is 20% of the mass of the in-situ soil sample; the amount of alkali activator added is 12% of the precursor.

[0041] Example 7:

[0042] Weigh 5 parts by weight of montmorillonite, 10 parts by weight of carbide slag, and 85 parts by weight of mineral powder and fly ash, and weigh them in a ratio of 7:3. Mix and stir at low speed for 2 to 3 minutes to prepare a solid waste mixture (precursor); prepare 12 parts by weight of 0.8 modulus sodium water glass and set aside. Then add an alkali activator and an appropriate amount of water (so that the water-binder ratio reaches 0.6) to the weighed solid waste mixture and stir for 5 minutes to obtain a curing agent. Then add the in-situ soil sample to the curing agent and stir evenly. The amount of curing agent added is 20% of the mass of the in-situ soil sample; the amount of alkali activator added is 12% of the precursor.

[0043] Comparative Example 1:

[0044] Weigh 5 parts by weight of montmorillonite, 10 parts by weight of carbide slag, and 85 parts by weight of mineral powder and fly ash in a ratio of 9:1. Mix and stir at low speed for 2-3 minutes to prepare a solid waste mixture. Then, add an appropriate amount of water to the solid waste mixture and stir for 5 minutes to obtain a solidifying agent. This solidifying agent is then added to the in-situ soil sample and stirred evenly. The amount of solidifying agent added is 20% of the mass of the in-situ soil sample.

[0045] Note: Compared with Example 3, this comparative example does not add sodium water glass.

[0046] Comparative Example 2:

[0047] Weigh 20 parts by weight of montmorillonite, 10 parts by weight of carbide slag, and 85 parts by weight of mineral powder and fly ash in a ratio of 9:1. Mix and stir at low speed for 2 to 3 minutes to prepare a solid waste mixture (precursor). Add 12 parts by weight of 0.8 modulus sodium water glass and set aside. Then add an alkali activator and an appropriate amount of water (so that the water-binder ratio reaches 0.6) to the weighed solid waste mixture and stir for 5 minutes to obtain a curing agent. Then add the in-situ soil sample to the curing agent and stir evenly. The amount of curing agent added is 20% of the mass of the in-situ soil sample; the amount of alkali activator added is 12% of the precursor.

[0048] Note: Compared with Example 3, the amount of montmorillonite added in this comparative example is 20 parts by weight.

[0049] Comparative Example 3:

[0050] Weigh 5 parts by weight of montmorillonite, 10 parts by weight of carbide slag, and 85 parts by weight of mineral powder and fly ash in a ratio of 5:5. Mix and stir at low speed for 2 to 3 minutes to prepare a solid waste mixture (precursor); prepare 12 parts by weight of 0.8 modulus sodium water glass for later use. Then add an alkali activator and an appropriate amount of water (so that the water-binder ratio reaches 0.6) to the weighed solid waste mixture and stir for 5 minutes to obtain a curing agent. Then add the in-situ soil sample to the curing agent and stir evenly. The amount of curing agent added is 20% of the mass of the in-situ soil sample; the amount of alkali activator added is 12% of the precursor.

[0051] Note: Compared with Example 3, the ratio of mineral powder to fly ash in this comparative example is 5:5.

[0052] Comparative Example 4:

[0053] Weigh 5 parts by weight of montmorillonite, 10 parts by weight of carbide slag, and 85 parts by weight of mineral powder, mix and stir at low speed for 2-3 minutes to prepare a solid waste mixture (precursor); add 12 parts by weight of 0.8 modulus sodium water glass and set aside. Then, add an alkaline activator and an appropriate amount of water (to achieve a water-binder ratio of 0.6) to the weighed solid waste mixture and stir for 5 minutes to obtain a curing agent. Then, add the in-situ soil sample to the curing agent and stir evenly. The amount of curing agent added is 20% of the mass of the in-situ soil sample, and the amount of alkaline activator added is 12% of the precursor.

[0054] Note: Compared with Example 3, this comparative example does not add fly ash.

[0055] Comparative Example 5:

[0056] Weigh 10 parts by weight of carbide slag, 85 parts by weight of mineral powder and fly ash in a ratio of 9:1, mix and stir at low speed for 2 to 3 minutes to prepare a solid waste mixture (precursor); prepare 12 parts by weight of 0.8 modulus sodium water glass and set aside. Then add an alkali activator and an appropriate amount of water (so that the water-binder ratio reaches 0.6) to the weighed solid waste mixture and stir for 5 minutes to obtain a curing agent. Then add the in-situ soil sample to the curing agent and stir evenly. Among them, the amount of curing agent added is 20% of the mass of the in-situ soil sample; the amount of alkali activator added is 12% of the precursor.

[0057] Note: Compared with Example 3, this comparative example does not add montmorillonite.

[0058] Standard test specimens were made from the soil samples obtained in Examples 1 to 7 and Comparative Examples 1 to 5, and unconfined compressive strength tests were performed after curing for 7 days and 28 days. The test indicators of different mix ratios are shown in Table 1.

[0059] The standard specimens (standard curing) obtained in Examples 1 to 7 and Comparative Examples 1 to 5 were then immersed in an acidic solution and a sulfate solution for 7 days, 14 days, and 28 days, and then unconfined compressive strength tests were performed. The test indicators of the examples under different corrosive environments are shown in Table 2.

[0060] Table 1 Test results of different ratio examples

[0061]

[0062] Table 2 Example test results under different corrosion environments

[0063]

[0064] The test results of the above examples are shown in Table 1. It can be seen from the test that when the curing agent provided by the embodiment of the present invention is applied to cement soil mixing piles, the compressive strength of the geopolymer solidified soil formed meets the relevant standards, and the performance is even better under curing at a temperature of forty degrees Celsius. Examples 1-3 illustrate that when the amount of alkali activator added is 12% and the modulus is 0.8, the compressive strength improvement for short-term curing (7d) is most obvious, and Examples 3-5 illustrate that the modulus of the alkali activator should not be too high or too low, as too high or too low will affect its compressive strength. Example 3, Examples 6 and 7 illustrate that the optimal dosage ratio of mineral powder to fly ash is 9:1. In all examples, the acidic solution has a greater effect on the compressive strength of the specimens, while the compressive strength of the specimens in the sulfate solution is relatively stable, but the compressive strength of the specimens after 7, 14 and 28 days of immersion is not less than 1.5 MPa Meets the requirements.

[0065] In Comparative Example 1, without the addition of sodium silicate, the compressive strength of the soil sample decreased significantly. The decrease in compressive strength became more pronounced as the immersion time in the corrosive solution increased.

[0066] In Comparative Example 2, the montmorillonite content exceeded the specified range of the present invention, resulting in a decrease in the compressive strength of the soil sample. Initially, the compressive strength increased slightly during immersion in the sulfate solution. This is due to the montmorillonite's strong water absorption, which allows it to absorb water and increase the material's compactness. Furthermore, its strong adsorption properties allow it to capture sulfate ions, reducing sulfate erosion on the geopolymer structure. As the immersion time increases, the material experiences greater internal expansion stress due to the increased proportion of montmorillonite added, leading to the appearance of microcracks and a decrease in compressive strength, indicating that excessive montmorillonite is not recommended.

[0067] In Comparative Example 3, the mixing ratio of fly ash and mineral powder exceeded the specified range of the present invention, and the compressive strength of the soil sample decreased. After being soaked in the corrosive solution, the compressive strength of the specimen was significantly reduced.

[0068] In Comparative Example 4, fly ash was not added, and the compressive strength of the soil sample decreased. Not adding fly ash will lead to less NASH gel formation in the material and the chemical corrosion resistance of the material will decrease, indicating that the amount of fly ash added should not be too low.

[0069] In comparative example 5, montmorillonite was not added, and the compressive strength of the soil sample decreased. During the soaking stage, due to the lack of montmorillonite, the crack resistance of the test piece was weakened. Under the corrosion of sulfate, cracks began to form and expand, resulting in a decrease in the compressive strength of the test piece after soaking, indicating that the amount of montmorillonite added is not easy to be too low. The present invention adopts industrial by-products such as montmorillonite, mineral powder, fly ash, and calcium carbide slag as the main curing materials, and makes them into curing agents through different proportions. The application of the present invention to cement-soil mixing piles not only meets the strength requirements, but also can produce significant benefits in terms of environmental protection and energy saving. It provides a kind of efficient, economical and environmentally friendly solution for foundation treatment under complex engineering conditions, and has important technology promotion value and market application prospects.

[0070] Although the embodiments of the present invention have been disclosed above, they are not limited to the applications listed in the description and the embodiments. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and illustrations shown and described herein.

Claims

1. A cement soil mixing pile curing agent resistant to groundwater corrosion, characterized in that: The raw material components of the groundwater corrosion-resistant cement soil mixing pile curing agent include, by weight: 1 to 5 parts of montmorillonite, 10 to 20 parts of carbide slag, 70 to 85 parts of a mixture of mineral powder and fly ash, and 8 to 12 parts of sodium silicate activator; the mass ratio of mineral powder to fly ash in the mixture of mineral powder and fly ash is 7:3 to 9:

1.

2. The cement soil mixing pile curing agent resistant to groundwater corrosion according to claim 1, characterized in that: The mineral powder is S95 mineral powder, and the activity indexes after 7 days and 28 days are 412% and 86% respectively.

3. The cement soil mixing pile curing agent resistant to groundwater corrosion according to claim 1, characterized in that: The fly ash is Class F II fly ash with a fineness of 20%.

4. The groundwater corrosion resistant cement soil mixing pile curing agent according to claim 1, characterized in that: The montmorillonite has a particle size of 1-10 microns and a purity of more than 90%.

5. The groundwater corrosion resistant cement soil mixing pile curing agent according to claim 1, characterized in that: The modulus of the sodium water glass base activator is 0.8 to 1.

2.

6. A method for preparing a cement-soil mixing pile curing agent resistant to groundwater corrosion, characterized in that: The steps include: Step 1: Raw material preparation: prepare the raw materials according to the formula of the cement soil mixing pile curing agent resistant to groundwater corrosion according to any one of claims 1-5; Step 2: Adjust the modulus: Use an instrument to measure the modulus of the sodium silicate alkali activator to ensure that it is within the range of 0.8 to 1.2; if the modulus is too high, add NaOH solution to reduce the modulus; if the modulus is too low, add sodium silicate solution to increase the modulus to obtain the sodium silicate alkali activator; Step 3: Ratio design: weigh the raw materials according to the formula of the cement soil mixing pile curing agent resistant to groundwater corrosion according to any one of claims 1-5; Step 4: Mix the weighed montmorillonite, carbide slag, mineral powder and fly ash and stir at a low speed for 2 to 3 minutes to ensure that the mixture is uniform to obtain a precursor; Step 5: Add sodium silicate alkali activator to the precursor and continue stirring for 5 to 10 minutes to obtain a cement soil mixing pile curing agent resistant to groundwater corrosion.

7. The method according to claim 6, characterized in that In the step 4, a stirrer is used for low-speed stirring, and the rotation speed of the low-speed stirring is 48 rpm; in the step 5, the stirring speed is 100 rpm.

8. A method for using a cement soil mixing pile curing agent resistant to groundwater corrosion, characterized in that: The cement soil mixing pile curing agent resistant to groundwater corrosion is as described in claim 7; in the step 5, the sodium water glass alkali activator is mixed with water so that the water-binder ratio reaches 0.6, and then the precursor is added and stirred for 5 to 10 minutes to obtain the cement soil mixing pile curing agent resistant to groundwater corrosion, and then added to the in-situ soil sample and stirred evenly, and naturally cured after stirring. After curing is completed, the quality of the mixing pile is tested; wherein, the quality of the cement soil mixing pile curing agent resistant to groundwater corrosion is 20% of the in-situ soil sample.

Citation Information

Patent Citations

  • Micro-expansion early strength type low-calcium fly ash-based alkali-activated material and preparation method thereof

    CN105523723A

  • Geopolymer grouting material and preparation method thereof

    CN108409214A

  • Multi-solid-waste-based chlorine-salt-corrosion-resistant geopolymer concrete material and preparation method thereof

    CN117865583A

  • Composite curing agent for curing soft soil by using carbide slag and caustic soda flakes as excitants and curing method thereof

    CN117987146A